Strategy To Increase The Competence Of Practical Supervisors In The Learning Process Of Midwifery Students - Lilik Susilowati; Haura Karlina; Aulia Hervi Anggraini; Wahyu Wismanto Hadi (International Journal of Health and Pharmaceutical (IJHP), 2024)
Higher education has the function of developing the ability in order to educate the life of the nation in accordance with the vision, mission and goals of Higher Education. In producing competent and competitive graduates, every university must adjust to the national standards of education that have been set.  The scope of the national standard of education, the standard of educators and Educational Personnel states that, educators must have academic qualifications and competencies as learning agents, be physically and spiritually healthy, and have the ability to realize the goals of National Education. As vocational education, in the core curriculum of Diploma III Midwifery Education, the percentage of practical learning experience is set at 60 %. Competent practice mentors will contribute to producing midwifery graduates who can be used to become midwifery professionals. In order to improve the competence of the practice supervisor, one of them is the development of skills through education and training. This study aims to describe the management of education and training as improving the competence of practice supervisors in the College of Health Sciences. Improvement of the competence of the practice supervisor through the practice supervisor learning training is carried out through several stages, namely 1) analysis of the needs of the practice supervisor Learning Training, 2) design and planning of the practice supervisor Learning Training, 3) curriculum development of the practice supervisor learning training, 4) implementation of the practice supervisor learning training, 5) evaluation of the practice supervisor learning training, 6) obstacles and carrying capacity of the practice supervisor learning training. To achieve this goal, the research was conducted using a qualitative approach with a case study method on STIKes Abdi Nusantara and STIKes BPI. Data were collected using in-depth interviews, observations, and documentation studies. The data of this study were checked for correctness, reliability through triangulation process. The results showed that the process of implementation of the teaching and learning practice supervisor in the College studied went well. Education and training provided to the practice supervisor contributes positively to the competence of the practice supervisor.